2007
DOI: 10.3113/fai.2007.0005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lateral Instability: Arthroscopic Findings and Long-Term Results

Abstract: A high percentage of patients with lateral ankle instability have intra-articular pathology. Excellent results can be expected in patients with ankle instability who undergo arthroscopic treatment of associated intra-articular pathology and the modified Broström procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
181
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(189 citation statements)
references
References 44 publications
1
181
1
4
Order By: Relevance
“…Although many patients are successfully treated nonoperatively, residual problems may occur [4,8]. Twenty to 40% of patients with chronic instability have associated disorders, such as chondral lesions of the talus, peroneal tears, or loose bodies [2,3,7]. These lesions may contribute to morbidity after an ankle sprain [7,10,19,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many patients are successfully treated nonoperatively, residual problems may occur [4,8]. Twenty to 40% of patients with chronic instability have associated disorders, such as chondral lesions of the talus, peroneal tears, or loose bodies [2,3,7]. These lesions may contribute to morbidity after an ankle sprain [7,10,19,24].…”
Section: Introductionmentioning
confidence: 99%
“…Often patients arrive for surgical consultation with MR images obtained and read at outside institutions, which may add additional variability to the scenario. Some authors have recommended routine ankle arthroscopy to detect intraarticular disorders at the time of ligament reconstruction [3,7,10].…”
Section: Introductionmentioning
confidence: 99%
“…106,184,422 Later, studies reported OCD rates of 19% to 21% in patients with chronic ankle instability. 127,242 An incidence of up to 71% has been reported in patients with ankle fractures. 11,259,376 …”
Section: Epidemiologymentioning
confidence: 99%
“…The other most common sites are talar dome and capitellum. For OCL of talar dome, an incidence of 27 per 100,000 people has been reported [10]. Capitellum is the most commonly involved area in the elbow and is increasing in incidence at the most rapid rate [11].…”
Section: What Areas Does Ocl Involve?mentioning
confidence: 99%